P-37 General practitioner perceptions of current services for heart failure patients: a qualitative study. (1st March 2017) - Chen, Jingwen Jessica; Orr, Kathryn; Stone, Carol; Graham, Lisa; Doherty, Jennifer; McGlade, Kieran; Donnelly, Patrick
Abstract : Background: The holistic needs of patients with symptomatic heart failure are often neglected. This may be partly attributable to a reliance on secondary care management. It is proposed that collaboration and communication between Primary Care, Cardiology and Palliative Care Services may be key in meeting the multidimensional needs of patients. This qualitative study assesses the adequacy of current services within Northern Ireland, to meet the needs of patients with heart failure, as perceived by General Practitioners (GPs). Method: Semi-structured interviews were conducted with GPs recruited via the University Department of General Practice and Northern Ireland Medical and Dental Agency. Interviews were transcribed, independently coded using NVivo 9 TM and analysed using a six-step thematic analysis approach. Key themes were identified inductively. Results: Twenty semi-structured interviews with participants from each of the five Trust areas were conducted. GPs reported prioritising acute medical problems with less emphasis on the assessment of underlying needs. Discussions around end of life care were frequently neglected, related to poor awareness of the need to initiate these discussions, difficulties identifying palliative requirements and fear of causing unnecessary distress. Care provided by the heart failure team was highly regarded, although difficulties included inequity of access and inadequate handover to GPs. Specialist Palliative Care (SPC) services were deemed important, yet GPs often reported poor awareness of their role. The common perceptions that SPC services were overstretched; cancer focused and lacked expertise in heart failure lead to its limited utilisation. The need for these services to be community based was evident. Conclusions: GPs identified a number of barriers that currently limit the delivery of holistic care for community based heart failure patients. Expansion of the community heart failure service, more frequent conversations with patients, along with greater interdisciplinary collaboration and education may help bridge the current gaps in care provision.